2002
DOI: 10.3168/jds.s0022-0302(02)74053-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ascorbic Acid and l-Histidine Therapy on Acute Mammary Inflammation in Dairy Cattle

Abstract: Ascorbic acid and L-histidine were investigated as antioxidant therapies for acute mammary inflammation. Mastitis was induced in eight nonpregnant Holstein cows by intramammary infusion of endotoxin. Treatments were administered in a 4 x 4 Latin square crossover design with 1-wk periods between challenges with endotoxin. Four individual treatments, control, ascorbic acid only, L-histidine only, and ascorbic acid plus L-histidine, were applied. Two doses of 25 g of ascorbic acid administered intravenously at 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 19 publications
1
22
0
3
Order By: Relevance
“…For example, common diseases such as pneumonia (15), enteritis (16) and septicemia in pigs (17) are caused by disorders in antioxidant homeostasis. The administration of antioxidants can protect animals from these diseases or reduce their clinical symptoms (18). In addition, studies have shown that animals at an early age have a low antioxidant system compared to adults (19,20), and so it is more important to administer antioxidants to young animals for disease protection.…”
mentioning
confidence: 99%
“…For example, common diseases such as pneumonia (15), enteritis (16) and septicemia in pigs (17) are caused by disorders in antioxidant homeostasis. The administration of antioxidants can protect animals from these diseases or reduce their clinical symptoms (18). In addition, studies have shown that animals at an early age have a low antioxidant system compared to adults (19,20), and so it is more important to administer antioxidants to young animals for disease protection.…”
mentioning
confidence: 99%
“…A recent study indicated that plasma vitamin C level was decreased after the induction of mastitis in lactating cows [19]. Furthermore, vitamin C administration stimulated recovery from acute mammary inflammation in dairy cattle [4]. These reports suggested that stressed cattle possibly suffered from vitamin C deficiency.…”
mentioning
confidence: 99%
“…Diante disso, sugere-se que esses animais poderiam receber uma dieta suplementada com ASA, já que a mesma não é produzida de forma endógena e a fim de auxiliar no tratamento preservando o status oxidativo de vacas leiteiras quando elas se encontram em condições promotoras da síntese de ERs no organismo, minimizando assim a ocorrência de efeitos adversos em virtude do estresse oxidativo (40,41) . Cabe salientar que Chaiyotwittayakun et al (42) investigaram o efeito da administração de ácido ascórbico após induzir a inflamação da glândula mamária em vacas e evidenciaram que duas doses de 25 g administradas por via intravenosa em três e cinco horas após indução do processo inflamatório aumentam a recuperação da produção de leite em 9%, o que confirma a nossa indicação de suplementação de ASA no tratamento da mastite bovina.…”
Section: Resultsunclassified